Peningkatan Kualitas Penulisan Skripsi Bagi Mahasiswa STIA Muhammadiyah Selong - Robyan Bafadal (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Writing a thesis is still a mandatory requirement for obtaining a bachelor's degree. Even though at this time there are many non-thesis pathways that are graduation requirements, generally in Higher Education (PT) it is still a must. Then writing a thesis becomes a difficulty for students, not a few even drop out of campus because of difficulty writing a thesis. Therefore, the purpose of this community service activity is to help students prepare their thesis so as to improve its quality. So students can write a thesis according to their interests when studying. Students write their own thesis and do not use the services of other people in writing thesis. Using the services of other people in writing thesis certainly reduces the authority and intellect of students. The method or stages used to solve the target activity problem are as follows. Outreach to students about the requirements for thesis writing, Provision of Material on Procedures for Writing Thesis, Training, Assistance, and Thesis Writing Simulation. Students who took part in this activity looked enthusiastic because writing a thesis was a new world for them. The enthusiasm of the participants was seen from their persistence in following the material from the beginning to the end of the service. The fruit of enthusiasm and persistence in following the course of the event resulted in an understanding regarding how to write a good thesis marked by increased quality and faster completion time.